Pemberian Macam Konsorsium Bakteri Hasil Isolasi Tumbuhan Pantai pada Kangkung (Ipomoea reptans Poirs.) - Umul Aiman; Tantriati Tantriati; Bambang Sriwijaya (Universitas Muhammadiyah Yogyakarta, 2017)
Bacteria consortium isolated from coastal plant was used as Plant Growth Promoting Rhizobacteria (PGPR) which can improve the growth and yield of plant. The purpose of this research was to understand the effects of various bacteria consortium application on the growth and yield of water spinach. The research was conducted on June-September 2016 in Microbiology Laboratory, Agroindustry Laboratory and Agriculture Land, University of Mercu Buana Yogyakarta. The study used a single factor experiment with 16 treatments and 3 blocks which arranged using completely randomized design (CRD). The treatment was desinged by soaking the water spinach seed on the various PGPR consorcium. All treatments were control (seed soaking on the water or without PGPR), the seed soaking on the various PGPR consorsium including K2, K9, K15, C7, K2K9, K2K15, K2C7, K9K15, K9C7, K15C7, K2K9K15, K2K9C7, K9K15C7, K2K15C7, and K2K9K15C7. The economic weight of water spinach which soaking on K2K9K15C7 consorcium was the best treatments compare to other treatments. Application of single isolate including K2, K9, K15, C7 and rhizobacteria consortium including K2K9, K2K15, K2C7, K9K15, K9C7, K15C7, K2K9K15, K2K9C7, K9K15C7, K2K15C7 can improved the yield of water spinach compare to the treatment without application of rhizobacteria.